Factors that affect the performance of public project in Malaysia - Norsyahidatul Nazirah , Ismail (2012)
Public project is covers most of the infrastructure and facilities needs such as schools, hospitals, administration offices, religious buildings and many more. This paper based on study that has been conducted which involves types of public project and problems of handling public project. This study also focused on factors that affect the performance of public project in Malaysia. To achieve the objective of this study, 140 sets of questionnaire have been sending to twenty (20) companies and eight (8) Jabatan Kerja Raya (JKR) main branches around Malaysia. Average Index (AT) method have been use to analyze data that has been collected. It was found that, there are eleven (11) types of public project and the highest occurrence is public facilities project. Nevertheless, there are twelve (12) problems of handling public project in Malaysia and the highest frequency of occurrence is social issues. There are four factors that affect the performance of public project in Malaysia which are cost, time, quality and safety and health and the critical factor that affects the performance of public project is cost. Future study can be done about how to control the problems of handling public project in Malaysia which is can affect the performance of public project, how these four (4) factors which are cost, time, quality, and safety and health will affect the performance of public project, and how to control the factors that affect the performance of public project.